2006
DOI: 10.1002/cphc.200600201
|View full text |Cite
|
Sign up to set email alerts
|

Fickian Diffusion Constrained on Spherical Surfaces: Voltammetry

Abstract: A model is developed for the voltammetric response due to surface charge injection at a single point on the surface of a sphere on whose surface the electroactive material is confined. Accordingly, charge diffusion is constrained to the spherical surface and thus mimicks the voltammetric response of immobilised microparticles derivatised with electroactive material. The full cyclic voltammetric response is investigated, and the peak currents, the peak-to-peak separation and the symmetry of the voltammetric wav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
10
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 18 publications
3
10
0
Order By: Relevance
“…For many other cases of functionalized carbon nanotubes (or modified graphite electrodes), Compton et al also identified a square root of scan rate dependency of peak currents [31,32]. These findings have been explained on a theoretical basis by the (non-Cottrellian) propagation of charge on the carbon particle surface [33,34], whereby electrons are assumed to hop from one chemical moiety to another, all being attached to the particle surface, as depicted in Figure 6.7.…”
Section: Theory J183mentioning
confidence: 96%
See 3 more Smart Citations
“…For many other cases of functionalized carbon nanotubes (or modified graphite electrodes), Compton et al also identified a square root of scan rate dependency of peak currents [31,32]. These findings have been explained on a theoretical basis by the (non-Cottrellian) propagation of charge on the carbon particle surface [33,34], whereby electrons are assumed to hop from one chemical moiety to another, all being attached to the particle surface, as depicted in Figure 6.7.…”
Section: Theory J183mentioning
confidence: 96%
“…Thompson and Compton investigated, from a theoretical standpoint, the case of a spherical microparticle with an electroactive compound on its surface and attached to a solid electrode surface [33,34]. The movement of charge was assumed to start exclusively from the contact point (or line) between the microparticle and electrode (i.e., at the three-phase boundary, if an electrolyte phase is considered) and to proceed over the particle surface only (see also Section 6.3.1).…”
Section: Theory J183mentioning
confidence: 99%
See 2 more Smart Citations
“…10 can be constructed [67]. Compton et al have provided theoretical modeling of charge diffusion on the surface of immobilized spherical particles [67], voltammetry at random microparticle arrays [68], and dissolution of microparticle arrays [69] and nanoparticle detection [70]. Direct oxidation of the Ag nanoparticles during collision events was monitored by the presence of a spike under oxidative current.…”
Section: Electrochemical Characterization Of Nanoparticlesmentioning
confidence: 99%